Distribution Strategy to Mauquf to Create the Trust of Nazir - Manaanu , Yusuf Al; Wibowo , Hendri Setyo; Ulum , Bahrul (Al-Insyiroh: Jurnal Studi Keislaman, 2021)
Waqf assets that are well managed and developed according to a clear direction can increase the economic level of the community with the economic means therein. The role of Waqf nazir becomes very important considering their duties, namely, the manager, as well as the Waqf object service, according to their functions. Of course, this is related to mauquf 'alaihi, in which they are appointed to benefit from the allocation of Waqf. The purpose of this research is to look at the mauquf ' alaih strategy in maintaining Nazir's trust so that the assets of the Waqf were maintained and well maintained. The method used in this research is descriptive qualitative research with a literature study approach, which will explain about Waqf. The type of data used in this scientific paper is secondary data. The data sources referred to are journals and books on Waqf management. However, the results show that the management of Waqf assets has a very significant impact and produces greater benefits if it is managed and developed productively. Then the role of nazir will be seen as more visible considering that they are the ones in the workshop for the Waqf. Economic opportunities in productive Waqf can boost nazir's confidence and encourage him to be more active in the organization and Waqf